Characteristics of sea trout spawners (Salmo trutta) in the Vistula River mouth in reference to the previous Vistula River stocks - Buras, Paweł (Fisheries & Aquatic Life, 2020)
The age structure and length distribution of sea trout spawners caught in the Vistula River mouth in the 1984–1986 period were analyzed in reference to previous Vistula stocks of summer spawning and winter spawning runs, and also to silvering sea trout. The comparison took into consideration two variants: the period when the sea trout summer spawning and winter spawning runs ascended the Vistula and when they gathered at spawning grounds. Statistically significant differences were confirmed in the age structure and length distribution of sea tout spawners caught in the Vistula River mouth in the 1980s and the previous Vistula stocks. The reason for these difference must be sought in management interventions and especially in the permanent cycle of smolt production, sea trout spawner selection when they ascended the Vistula, catches made for artificial spawning, and the periodic stocking of sea trout with material originating from Pomeranian rivers.